Development and effectiveness of tuberculosis risk score for smokers in tuberculosis screening uptake and detection - Khalid, Tengku Noor Farhana Tengku (2022)
Background: Tuberculosis (TB) remained one of the major infectious diseases worldwide. Smokers are considered as high-risk for TB disease. Many TB cases are still undetected, especially among the smoker population. Objective: To determine the factors associated with TB diseases among the smoker population, developing, validating, and evaluating the effectiveness of the Tuberculosis Risk Score for Smoker (TBRSS) in Bachok, Kelantan. Method: This study consists of three phases. The case-control study in phase 1 consists of 159 patients comparing patients with TB and those without the disease. Their smoking status was either active, ex- or passive smokers aged 18 years and above. The patients were interviewed using proforma (45 items). Simple and multiple logistic regressions were applied to analyse the data. In Phase 2, the risk score was derived from multiple logistic regression or decision tree classification analysis. The content validation study involved eight TB experts. Values were obtained for factor content-validity index (F-CVI) and scale-level content validity index, averaging index (S-CVI/Ave). Twenty healthcare workers (HCWs) in health clinics were selected for the face validation study and face validity index (FVI) values were obtained. The quasi-experimental study in phase 3 involved 156 participants 18 years and above known for their smoking status screened with TBRSS. The proportion of patients who underwent screening and diagnostic tests at different dates was noted. The number of smokers screened before and after implementing the TBRSS was noted. The difference between the regression line and R2 before and after were obtained based on interrupted time series analysis. Results: In the Phase 1 study, most participants are male with a median age of more than 40 years. The patients consisted of a mixed number of active, ex- and passive smokers. Almost all patients never had TB before. More than half of the patients had cough with sputum, did not have night sweat, no chest pain and no haemoptysis. The median duration of TB symptoms is 30 days for the cases and seven days for the controls. Four variables were significantly associated with TB disease: smoking status, presence of night sweat, significant weight loss and duration of TB symptoms. From that, two risk scores developed. The experts gave the F-CVI and S-CVI/Ave values of 0.83 and above, and the HCWs gave the FVI values of equal or more than 0.88. The TB experts chose the risk score derived from multiple logistic regression as the TBRSS. In the Phase 3 study, the accuracy of the TBRSS is 20.5%, with a sensitivity value of 80.0% and specificity value of 18.5%. The positive predictive value is 3.1% and the negative predictive value is 96.6%. Most participants (87.2%) had their diagnostic tests done on the same day with screening. The regression line improved with the R2 value changing from 0.064 to 0.160 during the intervention Conclusion: The TBRSS is a validated newly developed TB screening tool. It effectively increases the number of TB screenings among the smoker population. More studies need to be conducted to evaluate the usefulness of the TBRSS further.